Lipid metabolic reprogramming and associated ferroptosis in osteosarcoma: From molecular mechanisms to potential targets - Zhiyang Yin; Guanlu Shen; Minjie Fan; Pengfei Zheng (Journal of Bone Oncology)
Osteosarcoma is a common bone tumor in adolescents, which is characterized by lipid metabolism disorders and plays a key role in tumorigenesis and disease progression. Ferroptosis is an iron-dependent form of programmed cell death associated with lipid peroxidation. This review provides an in-depth analysis of the complex relationship between lipid metabolic reprogramming and associated ferroptosis in OS from the perspective of metabolic enzymes and metabolites. We discussed the molecular basis of lipid uptake, synthesis, storage, lipolysis, and the tumor microenvironment, as well as their significance in OS development. Key enzymes such as adenosine triphosphate-citrate lyase (ACLY), acetyl-CoA synthetase 2 (ACSS2), fatty acid synthase (FASN) and stearoyl-CoA desaturase-1 (SCD1) are overexpressed in OS and associated with poor prognosis.Based on specific changes in metabolic processes, this review highlights potential therapeutic targets in the lipid metabolism and ferroptosis pathways, and in particular the HMG-CoA reductase inhibitor simvastatin has shown potential in inducing apoptosis and inhibiting OS metastasis. Targeting these pathways provides new strategies for the treatment of OS. However, challenges such as the complexity of drug development and metabolic interactions must be overcome. A comprehensive understanding of the interplay between dysregulation of lipid metabolism and ferroptosis is essential for the development of innovative and effective therapies for OS, with the ultimate goal of improving patient outcomes.